Surrounding free will philosophy, psychology, neuroscience (Oxford Univ. Press, 2015)
"This volume showcases cutting-edge scholarship from The Big Questions in Free Will project, funded by a grant from the John Templeton Foundation and directed by Alfred R. Mele. It explores the subject of free will from the perspectives of neuroscience; social, cognitive, and developmental psychology; and philosophy (both traditional and experimental). The volume consists of fourteen new articles and an introduction from top-ranked contributors, all of whom bring fresh perspectives to the question of free will. They investigate questions such as: How do children conceive of free will and how does their concept of free will develop? How does lowered or raised confidence in the existence of free will affect our behavior? What modifies our power to resist temptation? What do lay folk mean by free will? What brain processes underlie decisions? How does the conscious experience of voluntary action contribute to the neural control of behavior? What are the neural differences between deliberate choosing and arbitrary picking? How do neuroscientific studies of decision making in monkeys bear on human free will? Is determinism compatible with free will? What can a proper understanding of causation tell us about free will? What is moral responsibility? Readers interested in the current and future direction of scholarship on free will find this volume essential reading"..